The Chilean Database Group - Arenas, Marcelo; Barceló, Pablo; Bravo, Loreto; Gutiérrez, Claudio; Pérez, Jorge; Reutter, Juan; Rodriguez, M. Andrea (Journal of Information and Data Management, 2013)
During the last 15 years, the chilean researchers on databases have built a strong and cohesive group with wide international visiblity. In the present article, we briefly survey the history of the group and describe the research done by the team in 5 big areas: Semantic web databases, graph databases, data exchange, access control policies, and spatial databases. We also describe the international collaboration networks of the group and the participation of the group members in the organization of AMW, the most important regional event in data management. We finish the article by explaining what are the next steps for the group and what are the plans to achieve them.